Energy security and environmental sustainability index of South Asian countries: A composite index approach. (November 2019) - Shah, S.A.A.; Zhou, P.; Walasai, G.D.; Mohsin, M.
Highlights: This study develops energy security and environmental sustainability index for South Asia. We select comprehensive, meaningful, and most relevant set of energy and environmental indicators. Mathematical programming approach is adopted for weighting and aggregation of indicators. Results reveal Bhutan as more energy secure and environmentally sustainable country in South Asia. Maldives obtained lowest ESESI score. Abstract: The concept of energy security has received significant attention in studies. However, most of the studies often ignored to integrate environmental aspect in the energy security assessment. Therefore, to measure the energy security and environmental sustainability of South Asian countries, this study develops a new index, i.e., Energy Security and Environmental Sustainability Index (ESESI), which combines energy and environmental indicators. The study presents an analysis of the period 2006–2017. The results show that Bhutan outperforms the rest of the countries in South Asia based on different indicators. Likewise, the overall ESESI score reveals Bhutan as more secure regarding energy security and environmental sustainability. India comes second in the region with a stable score followed by Sri Lanka, which substantially increased its performance over time. Pakistan is ranked fourth; however, the country experienced a decreasing trend of ESESI score. Nepal, Bangladesh, and Afghanistan follow the list with reduced scores. Maldives obtained the lowest ESESI score during the study period 2006–2017. Lowest ESESI implies that the Maldives is the least energy secure and environmentally sustainable country in the region. Based on the above findings, this paper recommends cross-border energy trade and increase in trans-regional renewable energy investments for long-term energy security and environmental sustainability in the region.